2016
DOI: 10.1213/ane.0000000000001287
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Pain Without Clear Etiology in Low- and Middle-Income Countries: A Narrative Review

Abstract: Globally, 8 of the top 12 disabling conditions are related either to chronic pain or to the psychological conditions strongly associated with persistent pain. In this narrative review, we explore the demographic and psychosocial associations with chronic pain exclusively from low- and middle-income countries (LMICs) and compare them with current global data. One hundred nineteen publications in 28 LMICs were identified for review; associations with depression, anxiety, posttraumatic stress, insomnia, disabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…The findings obtained in our study agree with observations made in previous investigations on other ethnic groups. The lifetime prevalence of low back pain was 54% in our study population of individuals aged 40+ years, which was higher than the prevalence reported in previous investigations of other study populations in other countries [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Urwin and colleagues estimated the frequency of musculoskeletal pain in different anatomical sites in an adult population in general medical practices in the Greater Manchester region in the UK [6].…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The findings obtained in our study agree with observations made in previous investigations on other ethnic groups. The lifetime prevalence of low back pain was 54% in our study population of individuals aged 40+ years, which was higher than the prevalence reported in previous investigations of other study populations in other countries [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Urwin and colleagues estimated the frequency of musculoskeletal pain in different anatomical sites in an adult population in general medical practices in the Greater Manchester region in the UK [6].…”
Section: Discussionmentioning
confidence: 63%
“…To date, information about the prevalence of low back pain and neck pain in Russia and factors associated with the occurrence of low back and neck pain in Russia have been largely missing. In addition, information on the prevalence of low back pain, thoracic spine pain and neck pain have been relatively scarce for all other regions worldwide [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“… 12 , 37 Unlike other research, we did not confirm the association between the number of APSs and income. 34 , 49 , 50 Generally, these observed discrepancies across studies are difficult to interpret and methodological variations with regard to participants/samples and pain site definitions, age range, data analysis, and perhaps geo-linguistic–cultural differences may be responsible. 44 …”
Section: Discussionmentioning
confidence: 99%
“…However, depending on the definition, it is estimated that 25–30% of the world’s adult population will suffer from chronic pain during their lifetime 6,16. In general, the prevalence is higher among women, older individuals and those with mental stresses, depression and anxiety 17,18. In a considerable proportion of those with chronic pain, the etiology is uncertain (Box 1).…”
Section: How Common Is Chronic Pain?mentioning
confidence: 99%